TILLAGE EFFECTS ON YIELD, WATER USE EFFICIENCY AND ROOT DEVELOPMENT OF PERAL MILLET (Pennisetum glaucum L.R.Br.) IN ARID ZONE - Patidar, M. (Journal of Soil and Water Conservation, 2022)
Soil tillage significantly affect the grain yield. Farmers' practice of planting with cultivator at 22.5 cm .spacing resulted in significantly reduced grain yield of 3.1 q/ha, compared to planting mw to row distances of 45 cm, but having cultivator tines at 22.5 cm spacing and followed by single disc harrowing,